'Do Not Privatize the Giant's Shoulders': Rethinking Patents in Plant Breeding. Issue 8 (August 2016) - Bjørnstad, Åsmund
Abstract : Intellectual property rights (IPRs) have increasing impacts on plant breeding. Not only varieties but also germplasm and technologies are protected. Intellectual property has also affected corporate concentration in the seed supply chain. While not very controversial in the USA, it is increasingly controversial in Europe after rulings on plant patents concerning nontransgenic crops in 2015. Both political and industry voices call for new interpretations or legislations. Industry initiatives have opened facilitated patent access systems designated 'free access, but not access for free'. Although praiseworthy, they are voluntary and so far limited to vegetable crops. This Opinion article suggests a mandatory system of declaring IPR use linked to variety registration. This compulsory licensing system with 'toll roads, not road blocks', is likely to reward IPRs without delaying breeding progress. Trends: Once considered 'the common heritage of mankind', plant germplasm resources have become enclosed through rights spanning from international conventions to national and civil laws. Patents and material transfer agreements increasingly limit the breeders' exception guaranteed by intergovernmental agreements. In 2015, the Enlarged Board of Appeals (EBA) effectively nullified the prohibition to patent 'plant and animal varieties and essentially biological processes'. Four European governments have introduced breeding exceptions in their patent laws, with Germany also excluding 'essentially biological processes'. Since 2012 industry has launched patent pools and e-licensing to facilitate access. NGOs address patents from a food security perspective.